Environmental-friendly yellow pigment based on Tb and M (M=Ca or Ba) co-doped Y2O3 - De la Luz, Verónica; Prades, Marta; Beltrán, Héctor; Cordoncillo, Eloisa (Journal of the European Ceramic Society, 2013)
A yellow inorganic ceramic pigment with general formula Y1.86−xMxTb0.14O3−x/2 (M=Ca and/or Zn) with x=0.06, 0.32 and 0.64 were synthesized by a modified Pechini method. XRD, SEM and HRTEM/EDX analysis showed the formation of solid solution at 1300°C when x=0.06 and 0.32. The best b* yellow coordinates were obtained for Ca and Zn co-doped Y1.86Tb0.14O3 samples. The intensity of the yellow colour in the samples is related to the presence of Tb4+ ions. Samples with higher concentration of Tb4+ ions lead to a better yellow colour. The chemical stability of these pigments was determinate in an industrial glaze. The glazing tests indicated that the powder samples with x=0.06 and 0.32 fired at 1300°C were stable in the glaze. These results make it a potential candidate for environmental friendly yellow ceramic pigment to be used in applications such as pigment for glazes or inkjet printers.